Differing Clinical Courses and Prognoses in Patients With Gastric Neuroendocrine Tumors Based on the 2010-WHO Classification Scheme. Issue 44 (November 2015) - Kim, Beom Su; Park, Young Soo; Yook, Jeong Hwan; Oh, Sung Tae; Kim, Byung-Sik
Abstract : Abstract: The aim of this study is to test the prognostic accuracy of the 2010-WHO classification for postsurgery survival in nonmetastatic gastric neuroendocrine tumor (NET) cases. Whether the 2010-WHO classification of NETs can predict relapse after surgical resection has not yet been established. We selected 175 nonmetastatic gastric NET patients at Asan Medical Center, Seoul, Korea between 1996 and 2013. All tumors were classified using the WHO-2010 scheme. Among 175 patients with gastric NETs, we diagnosed 39 cases as WHO grade 1, 13 cases as grade 2, 66 cases as grade 3 (neuroendocrine carcinomas; NECs), and 57 cases as mixed with adenocarcinoma. Patients with grade 3 had a lower relapse-free survival (RFS) and overall survival (OS) than those with WHO grade 1/2 and had a lower OS than patients with mixed type tumors. Patients with grade 1/2 had a better OS than patients with mixed type. There was no significant difference in RFS and OS between small and large cell type lesions. Among WHO grade 1/2 patients with ≤1 cm sized lesions, none exhibited lympho-vascular, perineural, mucosal, or submucosal invasion, and we detected no lymph node metastases or recurrences. Our findings strongly suggest that WHO grade 3 behaves more aggressively than adenocarcinoma. Additionally, the survival of cases with large and small cell NEC was similar. Among WHO grade 1/2 patients who had ≤1 cm lesions, none exhibited lympho-vascular, perineural, mucosal, or submucosal invasion and all could be treated by endoscopic resection or minimally invasive surgery without node dissection.